Pengaruh Aset, Dana Pihak Ketiga (DPK) dan Pembiayaan Terhadap Kinerja Keuangan Perbankan Syariah Tahun 2014-2023 - Yudianto, Yuda; Setiawan, Iwan (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
Islamic banking has a role as an intermediary institution, the main task of Islamic banking is to collect funds from the public in the form of deposits or third party funds, then channel these funds in the form of credit or financing while managing existing assets properly. Financing channeled to the public has an important meaning both for the community and for Islamic banking itself to be able to improve financial performance. One of the parameters to measure financial performance is Return On Asset (ROA). Indonesia is one of the countries with a financial services sector consisting of two working principles, namely conventional and sharia. The Islamic financial sector can play a role in encouraging the country's economic growth, especially through Islamic banking savings and financing services. The purpose of this study is to examine and analyze the effect of total assets, financing disbursed (PyD), third party funds (DPK), on Return on Assets (ROA), namely micro. This study uses secondary data from Islamic Banking Statistics (SPS) for the first quarter of 2014 to the fourth quarter of 2023 in aggregate from Islamic Commercial Banks (BUS), Islamic Business Units (UUS) and Islamic People's Financing Banks (BPRS). With time series data, the data processing technique used in this research is multiple linear regression with the Ordinary Least Square (OLS) method using Eviews 10 software to determine the relationship between the independent variable (X) and the dependent variable (Y). The results showed: Partially Total Asset, DPK, and PyD have a positive and significant influence on ROA (financial performance).